Analisis User Interface Website SIAM UNPRI Berbasis Eye Tracking - Indra, Evta; Farhan, Muhammad; Lumbanraja, Lamtiur Rondang Wulan; Karim, Anggie Monica; Mariyanti, Eka; Akbari, Deni Adha; Edison, Rizki Edmi (Prodi Sistem Informasi Universitas Dharma Andalas, 2024)
This research aims to analyze the visual attention of the User Interface/User Experience (UI/UX) of the Student Academic Information System (SIAM) website at Prima Indonesia University (Unpri) based on eye tracking to enhance user experience. Unpri, as a progressive educational institution, has utilized information technology to provide academic services for students through the online SIAM. However, the complexity of some features within the learning platform often poses difficulties for certain students in its usage. In order to improve the effectiveness and efficiency of the SIAM website, this research employs eye tracking methodology to observe users' eye movements while interacting with the website interface. The findings of this research are expected to provide valuable insights to the campus administration to enhance user experience, thus making the SIAM website a more effective and efficient system in supporting the learning process and academic administration at Unpri.